PERFORMANCE ANALYSIS OF AGRICULTURAL EXTENDERS IN NORTH ACEH DISTRICT - Nur Aini; Eva Wardah; Setia Budi; Hafni Zahara (Jurnal Mahasiswa Agribisnis, 2024)
The performance of agricultural extension workers is the result of work achieved by agricultural extension officers in North Aceh Regency in accordance with the duties and responsibilities given to him for the achievement of agricultural extension goals that have been set. This study aims to analyze the performance of agricultural extensionists in North Aceh district and to determine the relationship of extension characteristics with the performance of agricultural extension in North Aceh Regency. The analysis method used is descriptive qualitative and quantitative. The results showed that the performance of agricultural extension is in North Aceh District was very good with an average index value of 81.32%. There are two significant relationships between the characteristics of extension, namely the age and working period of the extension with the performance of extension workers at the stage of agricultural extension preparation with a significant value below 0.05 which is 0.039. The correlation coefficient is negative (-) which means that there is an indirect relationship between the age and working life of the extension and the performance of the extension.Keywords: Performance, Agricultural Extension, farmers